Social identity, competition, and finance: a laboratory experiment - Stefan Bauernschuster; Oliver Falck; Niels Daniel Große (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
There is extensive literature, both theoretical and empirical, on the effects of social identity on a wide range of economic and non-economic outcomes. However, there is only scarce knowledge about how social identity is affected by policies or market structure. We address the question how competition among suppliers of finance interacts with trust and trustworthiness in a laboratory one-shot trust game. In order to disentangle pure effects of competition and effects of competition that concern social identity, we apply a 2 x 2 treatment design. We induce social identity by letting subjects play coordination games with clear focal points, which leads to higher investments and trustworthiness in the trust game. Our results show that competition has no significant effects on trust and trustworthiness of individuals in a strangers' framework. However, in a framework with competition of in-group and out-group investors we see that competition leads to crowding out of social identity by reducing trustworthiness. We suggest that once competition comes into play, trustees see in-group trustors' investments as the outcomes of a competitive bidding process rather than voluntary trust, which crowds out reciprocity.
Keywords: C92; G11; Z13; L14; 330; Trust Game; Social Identity; Competition; Vertrauen; Spieltheorie; Soziale Beziehungen; Wettbewerb; Test